DESIGNING A COLLABORATIVE MULTILINGUAL DIGITAL STORYBOOK FOR INTERCULTURAL LEARNING THROUGH INDONESIAN AND JAPANESE FOLKTALES - Nurrahma Restia Fatkhiyati; Rizdika Mardiana; Muhammad Ali Hamdi; David Moeljadi; Tesaannisa Tesaannisa; Diyantari Diyantari; Eva Leiliyanti; Sauqi Maisan; Rafi Afzal Nawfal (Prodi Sastra Inggris UKI, 2026)
In the globalization era, the qualified education requires literacy mastery, intercultural competence, and foreign language skills as essential 21st‑century competencies. However, the persistence of low reading competence and limited intercultural awareness remains a significant challenge in both Indonesia and Japan. In response to those challenges, this research aims to develop a multilingual digital storybook based on multimodality as a learning medium to enhance intercultural competence through the Indonesian and Japanese folktales. The study employs a creative-based research methodology approach through the ADDIE development model, which consists of the stages of analysis, design, development, implementation, and evaluation. The resulting product is an interactive digital e-book entitled Indonesia–Japan Folktales: Timun Mas & Momotaro, presented in three languages, Indonesian, English, and Japanese, combining textual content, visual illustrations, and audio narration. The experiment of the product was conducted with Japanese students from Kanda University of International Studies (KUIS) enrolled in an intermediate-level Indonesian language course, involving such activities as interactive reading, discussion, reflection, and questionnaires. The findings indicate that the multimodal digital storybook effectively fosters student engagement, promotes reading motivation, and strengthens cross‑cultural understanding. Such effectiveness is reinforced by the integration of visual and audio elements that alleviate linguistic cognitive load, while the cross‑cultural narrative content fosters reflection and critical cultural awareness. Consequently, the multilingual and multimodal digital storybook serves as an effective medium for intercultural learning and contributes to the advancement of cultural literacy and the orientation of global education in the digital age.